(untitled) (Research, Society and Development, 2020)
Academic Leagues (LA) are non-profit organizations that aim to deepen the themes in a certain area of ​​study, being made up of undergraduate students and guided by professionals associated with the Higher Education Institution (IES). The LA comprise an organization relevant to academic training, in this case, the future professional nurse. However, it is possible to perceive the insufficiency of studies regarding the creation, implementation and consolidation of LA in Nursing and, more specifically, the Academic Leagues of Stomatherapy (LAET). The objective of this research is to report the experience about the creation and implementation of a LAET in a campus from the expansion and interiorization of Public Universities. This is a qualitative and descriptive experience report on the creation and implementation of a LAET at the UFRJ-Macaé Campus. In addition to steps such as idealization, meetings to define criteria, create and approve the statute, select binders, internal and external activities, it is possible to consider the reorganization of remote activities due to the COVID-19 pandemic, contemplating strategies for adapting to the new scenario. During the process of idealization, foundation and implementation of LACEnfE, challenges and possibilities were experienced with regard to protagonism and student engagement in its formation. The development of steps for the creation, foundation and implementation of LACEnfE, based on an organized structure, proved to be effective and can be considered a model to be referenced, facilitating and assisting the academic autonomy, participating in the process.